2018
DOI: 10.1172/jci98093
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bone fracture repair requires 24R,25-dihydroxyvitamin D3 and its effector molecule FAM57B2

Abstract: The biological activity of 24R,25-dihydroxyvitamin D3 [24R,25(OH)2D3] remains controversial, but it has been suggested that it contributes to fracture healing. Cyp24a1-/- mice, synthesizing no 24R,25(OH)2D3, show suboptimal endochondral ossification during fracture repair, with smaller callus and reduced stiffness. These defects were corrected by 24R,25(OH)2D3 treatment, but not by 1,25-dihydroxyvitamin D3. Microarrays with Cyp24a1-/- callus mRNA identified FAM57B2 as a mediator of the 24R,25(OH)2D3 effect. FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 62 publications
0
40
0
1
Order By: Relevance
“…New metabolite profiling methods based on LC-tandem MS are now able to detect a range of serum metabolites formed by CYP24A1, including 24,25(OH) 2 D 3 , 1,24,25(OH) 3 D 3 , and 25(OH)D 3 -26,23-lactone. It is questionable whether any of these metabolites are biologically active, although recent studies by St-Arnaud and colleagues (6) have suggested that 24,25(OH) 2 D 3 may act as an allosteric activator of FAM57B2 that is involved in the synthesis of lactosylceramide, providing a potential mechanism for an early hypothesized role for 24,25(OH) 2 D 3 in bone fracture healing. 1,24,25(OH) 3 D 3 is also of particular interest because recent estimates of its circulating level in mice suggest that this metabolite might contribute to the net biological activity of vitamin D 3 (7)(8)(9)(10).…”
Section: Vitamin D Undergoes Final Bioactivation In the Kidney Viamentioning
confidence: 99%
“…New metabolite profiling methods based on LC-tandem MS are now able to detect a range of serum metabolites formed by CYP24A1, including 24,25(OH) 2 D 3 , 1,24,25(OH) 3 D 3 , and 25(OH)D 3 -26,23-lactone. It is questionable whether any of these metabolites are biologically active, although recent studies by St-Arnaud and colleagues (6) have suggested that 24,25(OH) 2 D 3 may act as an allosteric activator of FAM57B2 that is involved in the synthesis of lactosylceramide, providing a potential mechanism for an early hypothesized role for 24,25(OH) 2 D 3 in bone fracture healing. 1,24,25(OH) 3 D 3 is also of particular interest because recent estimates of its circulating level in mice suggest that this metabolite might contribute to the net biological activity of vitamin D 3 (7)(8)(9)(10).…”
Section: Vitamin D Undergoes Final Bioactivation In the Kidney Viamentioning
confidence: 99%
“…CYP24A1 null mice also have a problem with fracture repair as 24R,25(OH) 2 D is able to bind to a GPCR, Fam57B2, and thereby stimulates lactosylceramide production and fracture repair . Whether this also applies to humans with bi‐allelic mutations has, however, so far not been reported .…”
Section: Cyp24a1mentioning
confidence: 99%
“…(76,77) CYP24A1 null mice also have a problem with fracture repair as 24R,25(OH) 2 D is able to bind to a GPCR, Fam57B2, and thereby stimulates lactosylceramide production and fracture repair. (78) Whether this also applies to humans with bi-allelic mutations has, however, so far not been reported. (77) Polymorphism of the CYP24A1 gene is responsible for modest genetic variability of serum 25OHD (as one of the 8 genes known so far to result in genetically predisposed higher or lower serum 25OHD concentrations).…”
Section: Cyp24a1mentioning
confidence: 99%
“…However, a very recent publication has provided, for the first time, evidence for a possible novel mechanism to explain acceleration of bone‐fracture repair. Matrineau et al .…”
Section: 25‐(oh)2d3mentioning
confidence: 99%
“…have identified and cloned an effector molecule named FAM57B2 that binds 24,25‐(OH) 2 D 3 and produces a lipid‐signalling molecule lactosyl ceramide (LacCer) thatmediates endochondral ossification during bone callus formation . Ablation of CYP24A1 gene or inactivation of Fam57b2 gene in chondrocytes caused loss of the bone‐healing effect while treatment with exogenous synthetic 24R,25‐(OH) 2 D 3 or lactosyl ceramide, but not 1,25‐(OH) 2 D 3 , restores the effect . It is not yet clear if other 24‐hydroxylated vitamin D analogues or even other vitamin D analogues in general can reproduce the same bone‐healing effect as 24R,25‐(OH) 2 D 3 at equivalent doses to those used here.…”
Section: 25‐(oh)2d3mentioning
confidence: 99%